2019
DOI: 10.7287/peerj.preprints.27963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aflatoxins in Uganda: an encyclopedic review of the etiology, epidemiology, detection, quantification, exposure assessment, reduction and control

Abstract: Uganda is predominantly an agricultural country where farming employ more than 60% of the population. Aflatoxins remain a scourge in the country, unprecedentedly reducing the value of agricultural foods and in high enough exposure levels, implicated for hepatocellular carcinoma, stunted growth in children and untimely deaths. This review synthetizes the country’s major findings in relation to the mycotoxin’s etiology, epidemiology, detection, quantification, exposure assessment, control and reduction in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 76 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…It is unlikely to be due to HIV (or its treatment) since liver cancer risk was not significantly related to HIV infection in a cohort study in Kampala 22 . Exposure to dietary aflatoxin is also known to be an important risk factor for liver cancer in Africa, 23 but there is little suggestion that there has been any substantial diminution in exposure in Uganda 24 …”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely to be due to HIV (or its treatment) since liver cancer risk was not significantly related to HIV infection in a cohort study in Kampala 22 . Exposure to dietary aflatoxin is also known to be an important risk factor for liver cancer in Africa, 23 but there is little suggestion that there has been any substantial diminution in exposure in Uganda 24 …”
Section: Discussionmentioning
confidence: 99%
“…In Northern Uganda, the use of shea (Vitellaria nilotica) butter, simsim (Sesame indicum L.), and groundnut (Arachis hypogea L.) pastes as substitutes for refined cooking oil and vaseline with the belief that the latter are carcinogenic is known. Unfortunately, recent reports have pointed out that some of these food items are contaminated with mycotoxins, particularly aflatoxins which are potential carcinogens [19,235].…”
Section: Traditional Concept Of Cancer In Ugandamentioning
confidence: 99%
“…3a-Hydroxytirucalla-8, 24-dien-21-oic, 3αhydroxytirucalla-7,24-dien-21-oic and 3β-fluorotirucalla-7,24-dien-21-oic acids [101], catechol (19), tyrosol, vanillic, and phloretic acids, limonene, phellandrenes, phydroxybenzaldehyde, dihydroxyphenylacetic acid, phydroxybenzoic acid, dihydroxybenzoic acid, pinoresinol, secoisolariciresinol [102], schweinfurthinol, coniferaldehyde, p-hydroxycinnamaldehyde, ligballinol, and amentoflavone [103] Cytotoxicity test on leukemia (CCRF-CEM) cells at 40 μg/mL showed that leaves and bark extracts induced more than 50% growth of this cell line. Fruit mesocarp oil extract and seed kernel oil extracts are expected to be vital for chemoprevention of cancers and other oxidative damage-induced diseases [104] Capsicum frutescens L. Capsaicin (20) and quercetin [105] Aqueous fruit extracts exhibited anticancer activity (though lower than capsaicin standard) when tested against prostate (PC-3) and breast (MCF-7) cancer cell lines in vitro [105] 8…”
Section: Anticancer Plants Used In Local Communities Of Ugandamentioning
confidence: 99%
See 1 more Smart Citation
“…Mycotoxins are secondary toxic metabolites of fungi that contaminate food in many different parts of the world with far-reaching consequences on human and animal health in addition to causing enormous economic losses [4][5][6][7][8]. Several studies have reported high mycotoxin levels in maize and peanuts from the East African community region [9][10][11][12][13][14][15]. Major mycotoxins of concern in maize and peanuts are Afl atoxins (AFT), Fumonisins (FBs), Zearalenone (ZEN), and Deoxynivalenol (DON) which are mainly produced by Aspergillus sp and Fusarium sp as shown in Table 2 [2,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%